STN EN 60045-1: 2001 (08 0030), Parné turbíny Časť 1 Špecifikácie - Jurík, Milan; Pavlík, Martin; Drahý, Jozef (Slovenský ústav technickej normalizácie, 2001)
Táto národná norma je identická s EN 60045-1: 1993 v čekej verzii